Guyton and Hall textbook of medical physiology - Hall, John E. (John Edward), 1946-; Hall, Michael E. (Michael Edward) (Philadelphia, PA : Elsevier, 2021)
"The world's foremost physiology textbook. Known for its clear presentation style, single-author voice, and focus on content most relevant to clinical and pre-clinical students, Guyton and Hall Textbook of Medical Physiology, 14th Edition, employs a distinctive format to ensure maximum learning and retention of complex concepts. A larger font size emphasizes core information while supporting information, including clinical examples are detailed in smaller font and highlighted in pale lavender - making it easy to quickly skim the essential text or pursue more in-depth study. This two-tone approach, along with other outstanding features makes this bestselling text a favorite of students worldwide. Key features include : offers a clinically oriented perspective written with the clinical and pre-clinical student in mind, bridging basic physiology with pathophysiology ; focuses on core material and how the body maintains homeostasis to remain healthy, emphasizing the important principles that will aid in later clinical decision making ; presents information in short chapters using a concise, readable voice that facilitates learning and retention ; contains more than 1,200 full-color drawings and diagrams - all carefully crafted to make physiology easier to understand ; features expanded clinical coverage including obesity, metabolic and cardiovascular disorders, Alzheimer's disease, and other degenerative diseases."--adapted from back cover
Unit I: Introduction to physiology: the cell and general physiology. Functional organization of the human body and control of the "internal environment" ; The cell and its functions ; Genetic control of protein synthesis, cell function, and cell reproduction -- Unit II: Membrane physiology, nerve, and muscle. Transport of substances through cell membranes ; Membrane potentials and action potentials ; Contraction of skeletal muscle ; Excitation of skeletal muscle: neuromuscular transmission and excitation-contraction coupling ; Excitation and contraction of smooth muscle -- Unit III: The heart. Cardiac muscle; the heart as a pump and function of the heart valves ; Rhythmical excitation of the heart ; Fundamentals of electrocardiography ; Electrocardiographic interpretation of cardiac muscle and coronary blood flow abnormalities: vectorial analysis ; Cardiac arrhythmias and their electrocardiographic interpretation -- Unit IV: The circulation. Overview of the circulation: pressure, flow, and resistance ; Vascular distensibility and functions of the arterial and venous systems ; The microcirculation and lymphatic system: capillary fluid exchange, interstitial fluid, and lymph flow ; Local and humoral control of tissue blood flow ; Nervous regulation of the circulation and rapid control of arterial pressure ; Role of the kidneys in long-term control of aterial pressure and in hypertension: the integrated system for arterial pressure regulation ; Cardiac output, venous return, and their regulation ; Muscle blood flow and cardiac output during exercise; the coronary circulation and ischemic heart disease ; Cardiac failure ; Heart valves and heart sounds:; valvular and congenital heart defects ; Circulatory shock and its treatment -- Unit V: The body fluids and kidney. Regulation of body fluid compartments: extracellular and intracellular fluids; edema ; The urinary system: functional anatomy and urine formation by the kidney ; Glomerular filtration, renal blood flow, and their control ; Renal tubular reabsorption and secretion ; Urine concentration and dilution; regulation of extracellular fluid osmolarity and sodium concentration ; Renal regulation of potassium, calcium, phosphate, and magnesium; integration of renal mechanisms for control of blood volume and extracellular fluid volume ; Acid-base regulation ; Diuretics and kidney diseases -- Unit VI: Blood cells, immunity, and blood coagulation. Red blood cells, anemia, and polycythemia ; Resistance of the body to infection I: Leukocytes, granulocytes, the monocyte-macrophage system, and inflammation ; Resistance of the body to infection II: immunity and allergy ; Blood types: transfusion; and tissue and organ transplantation ; Hemostasis and blood coagulation -- Unit VII: Respiration. Pulmonary ventilation ; Pulmonary circulation, pulmonary edema, and pleural fluid ; Principles of gas exchange; diffusion of oxygen and carbon dioxide through the respiratory membrane ; Transport of oxygen and carbon dioxide in blood and tissue fluids ; Regulation of respiration ; Respiratory insufficiency-pathophysiology, diagnosis, oxygen therapy -- Unit VIII: Aviation, space, and deep-sea diving physiology. Aviation, high altitude, and space physiology ; Physiology of deep-sea diving and other hyperbaric conditions -- Unit IX: The nervous system A: General principles and sensory physiology. Organization of the nervous system, basic functions of synapses, and neurotransmitters ; Sensory receptors, neuronal circuits for processing information ; Somatic sensations I: General organization, tactile and position senses ; Somatic sensations II: Pain, headache, and thermal sensations -- Unit X: The nervous system B: The special senses. The eye I: Optics of vision ; The eye II: Receptor and neural function of the retina ; The eye III: Central neurophysiology of vision ; The sense of hearing ; The chemical senses-taste and smell -- Unit XI: The nervous system C: Motor and integrative neurophysiology. Spinal cord motor functions; the cord reflexes ; Cortical and brain stem control of motor function ; Cerebellum and basal ganglia contributions to overall motor control ; Cerebral cortex, intellectual functions of the brain, learning, and memory ; The limbic system and the hypothalamus-behavioral and motivational mechanisms of the brain ; States of brain activity-sleep, brain waves, epilepsy, psychoses, and dementia ; The autonomic nervous system and the adrenal medulla ; Cerebral blood flow, cerebrospinal fluid, and brain metabolism --- Unit XII: Gastrointestinal physiology. General principles of gastrointestinal function-motility, nervous control, and blood circulation ; Propulsion and mixing of food in the alimentary tract ; Secretory functions of the alimentary tract ; Digestion and absorption in the gastrointestinal tract ; Physiology of gastrointestinal disorders -- Unit XIII: Metabolism and temperature regulation. Metabolism of carbohydrates and formation of adenosine triphosphate ; Lipd metabolism ; Proten metabolism ; The liver ; Dietary balances; regulation of feeding; obesity and starvation; vitamins and minerals ; Energetics and metabolic rate ; Body temperature regulation and fever -- Unit XIV: Endocrinology and reproduction. Introduction to endocrinology ; Pituitary hormones and their control by the hypothalamus ; Thyroid metabolic hormones ; Adrenocortical hormones ; Insulin, glucagon, and diabetes mellitus ; Parathyroid hormone, calcitonin, calcium and phosphate metabolism, vitamin D, bone, and teeth ; Reproductive and hormonal functions of the male (and function of the pineal gland) ; Female physiology before pregnancy and female hormones ; Pregnancy and lactation ; Fetal and neonatal physiology -- Unit XV: Sports physiology
Revised edition of: Guyton and Hall textbook of medical physiology / John E. Hall, PhD, Arthur C. Guyton Professor and Chair, Department of Physiology and Biophysics, Director, Mississippi Center for Obesity Research, University of Mississippi Medical Center, Jackson, Mississippi. 13th edition. [2016]
Includes bibliographical references and index
Keywords: Human physiology; Physiology, Pathological; Physiological Phenomena; Handboeken (vorm); Leermiddelen (vorm); Textbooks